ChemInform Abstract: Synthesis of Multi‐Substituted Vinylsilanes via Copper(I)‐Catalyzed Hydrosilylation Reactions of Allenes and Propiolate Derivatives with Silylboronates. Issue 48 (2nd December 2014) - Xu, Yun‐He; Wu, Liu‐Hai; Wang, Jun; Loh, Teck‐Peng
Abstract Multi‐substituted allenes with electron‐withdrawing groups, e.g. (I), (IV), and (VI) and propiolate derivatives (IX) react with silyl boronic acid ester (II) to afford silyl‐substituted butenoate derivatives (III), (V), and (VII)/(VIII) or β‐silyl‐substituted arylates (X), respectively.